The Extra-Territorial Applicability of the Principle of Non-Refoulement and Its Interception with Human Rights Law - Lamichhane, Shishir (Kathmandu School of Law Review, 2017)
The varying nature in treatment of refugees before and after the cold war is quite observable from the perspective of the ideological differences. The interest of asylum seekers was hardly promoted and protected in the absence of uniform state practices. It was further more affected because of non-reconciliation of the principle of non-refoulement and right of individuals to seek asylum. The paper talks about the challenges of the European Countries in framing policies and mechanisms to address the dysfunctionality of the refugee system. The paper further discusses the significance of international instruments and the extraterritorial application of those instruments along with mechanisms to address the problem of therefugees. The paper emphasizes on the duty of the states to take steps to ensure that the refugees must have 'protection somewhere' adhering to the principle of sharing burden/responsibility and to have a greater solidarity among the states.